2021
DOI: 10.34087/cbusbed.804112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of The Effects Of Different Storage Times On Pharmacological Agents Of Saffron (Crocus sativus L.) (Safranal, Crocin and Crocetin) and Their Quality Characteristics

Abstract: Bu çalışmanın temel amacı, safranın önemli farmakolojik ajanları (safranal, krosin ve krosetin) ve uçucu bileşenlerinin farklı depolama sürelerinde nasıl etkilendiğini belirlemektir. Gereç ve Yöntemler: Bu çalışmanın birinci aşamasında GC-MS/FID analizi ile safranın kalite kriterlerini belirlemede kullanılan önemli farmakolojik ajanlar olan safranal, crocin ve crocetin gibi temel bileşenlerin farklı depolama sürelerinin kalite üzerine etkileri araştırılmıştır. İkinci aşamada ise GC-MS/MS analizi ile stigma üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Ipek et al (2009) reported that they obtained the highest dry stigma yield of 583.1 g/d dry stigma from large (8 cm <) corm planting in the second year of the study. Reseults on the effects of different storage times on the amount of safranal, crocin, and crocetin showed that the amount safranal was between 1924.93 and 6164.79 mg/kg, the amount of crocin was between 55.43 and 296.20 mg/kg and, the amount of crocetin was between 1.67 and 5.13 mg/kg (Asil 2021a). In different locations in Turkey, the amount of safranal varied between 3253.14 and 22532.97 mg/kg, the amount of crocin was between 77.56 and 647.26 mg/kg in Hatay Yayladağı saffron, and the highest amount of crocetin was between 0.20 and 6.73 mg/kg in Ankara Ayas saffron (Asil and Goktürk 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipek et al (2009) reported that they obtained the highest dry stigma yield of 583.1 g/d dry stigma from large (8 cm <) corm planting in the second year of the study. Reseults on the effects of different storage times on the amount of safranal, crocin, and crocetin showed that the amount safranal was between 1924.93 and 6164.79 mg/kg, the amount of crocin was between 55.43 and 296.20 mg/kg and, the amount of crocetin was between 1.67 and 5.13 mg/kg (Asil 2021a). In different locations in Turkey, the amount of safranal varied between 3253.14 and 22532.97 mg/kg, the amount of crocin was between 77.56 and 647.26 mg/kg in Hatay Yayladağı saffron, and the highest amount of crocetin was between 0.20 and 6.73 mg/kg in Ankara Ayas saffron (Asil and Goktürk 2021).…”
Section: Resultsmentioning
confidence: 99%
“…For flame formation, 60 ml/min H2 (UHP grade), 400 ml/min air (zero grade), Helium (99.99%) as a carrier gas, and 10 ml/min flow rate were used as a gas mixture. The injector temperature was kept at 200 o C (Asil 2021a, Turkmen 2021.…”
Section: Methodsmentioning
confidence: 99%
“…and these photochemical substances are responsible for the color, aroma and taste of the saffron. 4 Crocetin is an aglycone part of naturally occurring crocin and is produced in biological systems as a hydrolytically bioactive metabolite. 5, 6 Studies on the pharmacological activities of crocetin have shown that this aglycone is a therapeutically useful bioactive metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile components of saffron samples were identified by GC-MS/MS (Hewlett-Packard 6890) instrument equipped with HP-5MS fused silica column (5% phenyl methyl polysiloxane 30 m 0.25 mm i.d.. film thickness 0.25 µm) and Hewlett-Packard mass selective detector 6890. GC-MS/MS analyses were carried out under the same conditions reported in the literature 4,19,20. …”
mentioning
confidence: 99%
See 1 more Smart Citation